2017
DOI: 10.3389/fspas.2017.00012
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Monitoring of the Broad-Line Region Properties in a Selected Sample of AGN

Abstract: We present the results of the long-term optical monitoring campaign of active galactic nuclei (AGN) coordinated by the Special Astrophysical Observatory of the Russian Academy of Science. This campaign has produced a remarkable set of optical spectra, since we have monitored for several decades different types of broad-line (type 1) AGN, from a Seyfert 1, double-peaked line, radio loud and radio quiet AGN, to a supermassive binary black hole candidate. Our analysis of the properties of the broad line region (B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
(75 reference statements)
1
18
0
Order By: Relevance
“…The correlation of oscillatory patterns in the continuum and emission lines of all objects (except Arp 102B), can be a consequence of a more general correlation trend between the continuum and emission lines fluxes of these objects (see discussion for correlation between continuum and Hβ emission lines of these objects in Ilić et al 2017). In addition, as time coverage of observations of NGC 4151 continuum is shorter then time coverage of observations of the Hα line, our study did not investigate how the weak (or even absent in some time periods) correlation between the continuum and emission line fluxes of this object (see details in Shapovalova et al 2008) would affect the detection of correlation of their oscillatory patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation of oscillatory patterns in the continuum and emission lines of all objects (except Arp 102B), can be a consequence of a more general correlation trend between the continuum and emission lines fluxes of these objects (see discussion for correlation between continuum and Hβ emission lines of these objects in Ilić et al 2017). In addition, as time coverage of observations of NGC 4151 continuum is shorter then time coverage of observations of the Hα line, our study did not investigate how the weak (or even absent in some time periods) correlation between the continuum and emission line fluxes of this object (see details in Shapovalova et al 2008) would affect the detection of correlation of their oscillatory patterns.…”
Section: Discussionmentioning
confidence: 99%
“…One can think that small variations in the light curves of E1821+643 (e.g. for the Hβ line Fvar ∼ 7%, see Ilić et al 2017), can be a reason that oscillatory patterns are not distorted. Based on the above discussion, NGC 5548 and E1821+643 represent dynamical extremes, the most chaotic and stable in our sample, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Note that recent reverberation studies showed that more luminous AGNs are scattered below the best-fit relation given by Bentz et al (2013); see §4.3 for more details. NGC 4395 Bentz et al 2013Du et al 2016Grier et al 2017Ilić et al 2017Park et al 2017Rakshit et al 2019 Figure 10. BLR radius vs. 5100Å AGN luminosity.…”
Section: Agn Luminosity and The Blr Radius-luminosity Relationmentioning
confidence: 99%
“…Best-fit relation by Bentz et al (2013, Clean+ExtCorr in Table 14) is shown as a black solid line, with the shaded region indicating the 1σ confidence interval of the fit and the dotted lines representing the 1σ prediction interval of AGNs considering intrinsic scatter. AGNs shown here are from Bentz et al (2013), as well as Du et al (2016Du et al ( , 2018, Grier et al (2017), Ilić et al (2017), Park et al (2017), and Rakshit et al (2019). NGC 4395 is shown as a blue circle with black error bar.…”
Section: Agn Luminosity and The Blr Radius-luminosity Relationmentioning
confidence: 99%
See 1 more Smart Citation